Location Advantages, Governance Quality, Stock Market Development and Firm Characteristics as Antecedents of African M&As - Tunyi Tunyi Abongeh (Journal of International Management, 2016)
This study explores firm- and country-specific antecedents of African M&As. We use one of the largest datasets to-date, consisting of 1490 unique African firms (11,183 firm-year observations) from 1996 to 2012 from 15 African countries. Our results suggest that improvements in time-varying country-level factors, including location advantages (market size, human capital and efficiency opportunities), national governance quality, and stock market development are associated with an increase in the volume of M&A activity. Consistent with the resource-curse paradox, high resource endowments are not associated with increased levels of M&A. In support of the management inefficiency, but contrary to the traditional firm size hypotheses, African targets are generally characterised by declining stock returns and accounting profitability, but are more likely to be larger firms; suggesting the presence of information asymmetry concerns in their selection. Notwithstanding, we find evidence of heterogeneity across countries with inconsistent support for the established target prediction hypotheses. Overall, our analysis suggests that a model which combines firm- and country-specific factors better explains the observed variations in African M&A activity.